DETERMINATION METHOD, DETERMINATION DEVICE, EXPOSURE DEVICE, AND PROGRAM - OKUDAIRA Yosuke (2020)
A determination method in which a formed image that is obtained from light that has been radiated at and reflected from a spatial light modulation element that has a plurality of pixels that are arranged at different locations in space, light that has been radiated at and transmitted by the spatial light modulation element, and/or light that has been radiated at and transmitted by a mask that has been virtually partitioned into a plurality of micro-regions that are regarded as the plurality of pixels is used to determine to which of a plurality of states each of the plurality of pixels should be set to form a target image in which a subject satisfies target conditions. The method involves: a setting step in which an evaluation function that makes the states of the plurality of pixels respectively correspond to the states of a plurality of bits of an Ising model and evaluates the coincidence between the formed image and the target image is set as a function for the plurality of bits; and a determination step in which, on the basis of the states of the plurality of bits as included in the results of evaluating the evaluation function using an Ising machine, it is determined to which of the plurality of states each of the plurality of pixels should be set. L'invention concerne un procédé de détermination selon lequel une image formée qui est obtenue à partir de la lumière qui a été rayonnée à et réfléchie par un élément de modulation de lumière spatiale qui a une pluralité de pixels qui sont agencés à différents emplacements dans l'espace, la lumière qui a été rayonnée à et transmise par l'élément de modulation de lumière spatiale, et/ou la lumière qui a été rayonnée à et transmise par un masque qui a été virtuellement partitionné en une pluralité de micro-régions qui sont considérées comme la pluralité de pixels est utilisée pour déterminer à quel état d'une pluralité d'états chacun de la pluralité de pixels devrait être réglé pour former une image cible dans laquelle un sujet satisfait des conditions cibles. Le procédé comprend : une étape de réglage dans laquelle une fonction d'évaluation qui mène les états de la pluralité de pixels à correspondre respectivement aux états d'une pluralité de bits d'un modèle Ising et évalue la coïncidence entre l'image formée et l'image cible est définie en tant que fonction pour la pluralité de bits ; et une étape de détermination dans laquelle, sur la base des états de la pluralité de bits tels qu'inclus dans les résultats d'évaluation de la fonction d'évaluation à l'aide d'une machine Ising, il est déterminé à quel état de la pluralité d'états chacun de la pluralité de pixels doit être réglé. 空間的に互いに異なる位置に配置された複数のピクセルを有する空間光変調素子に照明された光の反射光、透過光、および、仮想的に複数の微小領域に分割した前記複数の微小領域を前記複数のピクセルとみなしたマスクに照射された光の透過光、の少なくともいずれかを結像することにより得られる形成像により、対象物に目標とする条件を満たす像である目標像を形成するために、複数のピクセルそれぞれを、複数通りの状態の中の、いずれにすべきかを決定する決定方法であって、複数のピクセルのそれぞれにおける状態を、イジングモデルの複数のビットの複数の状態に対応させ、目標像と形成像の合致度を評価する評価関数を複数のビットの関数として設定する設定段階と、評価関数をイジングマシンで評価した結果に含まれる複数のビットの状態に基づいて、複数のピクセルのそれぞれについて、複数通りの状態のいずれにすべきかを決定する決定段階とを備える。